Assessing and promoting resilience in vulnerable children. - Daniel, Brigid, 1959- (J. Kingsley Publishers, 2002)
Helping practitioners in their work with vulnerable children of a school-going age, this workbook explores ways of nurturing resilience in different aspects of everyday life. Focusing on specific areas such as home life, talents and interests, the authors show how to make thorough assessments and intervene in constructive ways.